Diabetic retinopathy as an independent predictor of subclinical cardiovascular disease: baseline results of the PRECISED study. Issue 1 (29th December 2019) - Simó, Rafael; Bañeras, Jordi; Hernández, Cristina; Rodríguez-Palomares, José; Valente, Filipa; Gutierrez, Laura; González-Alujas, Teresa; Ferreira, Ignacio; Aguadé-Bruix, Santiago; Montaner, Joan; Seron, Daniel; Genescà, Joan; et al.
Abstract : Objective: Detection of subclinical cardiovascular disease (CVD) has significant impact on the management of type 2 diabetes. We examined whether the assessment of diabetic retinopathy (DR) is useful for identifying patients at a higher risk of having silent CVD. Research design and methods: Prospective case–control study comprising 200 type 2 diabetic subjects without history of clinical CVD and 60 age-matched non-diabetic subjects. The presence of subclinical CVD was examined using two parameters: (1) calcium coronary score (CACs); (2) composite of CACs >400 UA, carotid plaque ≥3 mm, carotid intima–media thickness ratio >1, or the presence of ECG changes suggestive of previous asymptomatic myocardial infarction. In addition, coronary angio-CT was performed. DR was assessed by slit-lamp biomicroscopy and retinography. Results: Type 2 diabetic subjects presented higher CACs than non-diabetic control subjects (p<0.01). Age, male gender, and the presence of DR were independently related to CACs >400 (area under the receiver operating characteristic curve (AUROC) 0.76). In addition, an inverse relationship was observed between the degree of DR and CACs <10 AU. The variables independently associated with the composite measurement of subclinical CVD were age, diabetes duration, the glomerular filtration rate, microalbuminuria, and the presence of DR (AUROC 0.71). In addition, a relationship (p<0.01) was observed between the presence and degree of DR and coronary stenosis. Conclusions: The presence and degree of DR is independently associated with subclinical CVD in type 2 diabetic patients. Our results lead us to propose a rationalized screening for coronary artery disease in type 2 diabetes based on prioritizing patients with DR, particularly those with moderate–severe degree.